A Prevalence of Imprinted Genes within the Total Transcriptomes of Human Tissues and Cells. (11th September 2012) - Anisimov, Sergey V.
Abstract : Genomic imprinting is an epigenetic phenomenon that causes a differential expression of paternally and maternally inherited alleles of a subset of genes (the so-called imprinted genes). Imprinted genes are distributed throughout the genome and it is predicted that about 1% of the human genes may be imprinted. It is recognized that the allelic expression of imprinted genes varies between tissues and developmental stages. The current study represents the first attempt to estimate a prevalence of imprinted genes within the total human transcriptome. In silico analysis of the normalized expression profiles of a comprehensive panel of 173 established and candidate human imprinted genes was performed, in 492 publicly available SAGE libraries. The latter represent human cell and tissue samples in a variety of physiological and pathological conditions. Variations in the prevalence of imprinted genes within the total transcriptomes (ranging from 0.08% to 4.36%) and expression profiles of the individual imprinted genes are assessed. This paper thus provides a useful reference on the size of the imprinted transcriptome and expression of the individual imprinted genes.